A Mechanism for Control on Teams Performance - Lambovska, Maya (Research Papers, 2014)
This paper presents a mechanism for control on teams performance that is based on contem-porary achievements of management and mathematical sciences. The mechanism is explained by conception, methodology and tools for control on teams. The author’s conception of teams control consists of three models: team model, model for teams control process and model for teams control system. Control models are based on a complex toolkit that includes classical managerial tools (method of focus groups and method of open inquiry) and modern mathe-matical tools of the theory of fuzzy logic and theory of fuzzy subsets (confidence intervals, fuzzy subsets, fuzzy trapezoidal numbers, fuzzy influence matrices, functions “experton” and fuzzy logic operations).Specifics of the teams control mechanism finds expression primarily in the way on which teams performance is understood and evaluated. In this study teams performance is evaluated by the tools of fuzzy logic. Specifics of the teams control mechanism is also associated with the combination of fuzzy techniques and tools for quantification of evaluations/forecasts, evaluation, study of joint and hidden influences.This paper is developed in three parts. Theoretical foundations of control on teams are worked out in the first part. Methodology and tools for control on teams are also proposed in this part.  The conceptual bases of the control on teams are elaborated in the second part. Three models, by which the conception of control on teams is described, are also presented in the second part. The third part summarizes main results from the approbation of the teams control con-ception.
Keywords: Тeams; Fuzzy logic; Control